Sistem Klasifikasi Kualitas Keju Mozzarella berdasarkan Warna dan pH menggunakan Metode Naive Bayes - Izaaz Waskito Widyarto; Dahnial Syauqy; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Mozzarella cheese is one type of cheese that is favored by the people of Indonesia, because it has elastic and melting texture properties that are different from other cheeses. Currently, in determining the quality of Mozzarella cheese, it is usually seen from the color and level of moisture, one example in determining the quality of Mozzarella cheese which is easy to see with the eye must be shiny and white like porcelain. The microcontroller used by Arduino Uno is because the method of use is not too difficult and very easy to use. This system uses a TCS3200 color sensor to measure the color of Mozzarella cheese, a pH sensor to measure acidity and Naive Bayes to predict the quality of Mozzarella cheese. The position of the TCS3200 color sensor is placed at the base facing up, for the measuring cup it is on top of the TCS3200 sensor. The point of placing the TCS3200 sensor is in a solid black acrylic due to reducing the entry of light from outside. While the pH sensor is placed above the measuring cup which is useful for taking the acidity value of Mozzarella cheese. Naive Bayes classification is used because it is very effective and requires quite a bit of training data, from the test results obtained 94% accuracy, the average accuracy of the color sensor TCS3200 is 98.07%, and the average accuracy of the pH sensor is 98.83%.